A Holocene Paleosecular Variation Record From the Northwestern Ross Sea, Antarctica - Olivia J. Truax; Faye Nelson; Christina R. Riesselman; Christian Ohneiser; Jae Il Lee; Kyu‐Cheul Yoo; Bob Dagg; Gary Wilson (Geochemistry, Geophysics, Geosystems)
Abstract We present a mid‐to‐late Holocene record of relative paleosecular variation from the Ross Sea region of Antarctica. The 6,700‐year‐long record of inclination, declination, and relative paleointensity from a marine sediment core collected near Cape Adare is independently dated using a combination of ramped pyrolysis oxidation and carbonate radiocarbon dates. Agreement between the large‐scale features of the relative paleointensity record and the virtual axial geomagnetic dipole moment suggests that changes in the record are dominated by the dipole component of the Earth's geomagnetic field. Correspondence between the record and a non‐independently dated reconstruction from the Antarctic Peninsula indicates regionally coherent changes in the geomagnetic field intensity in the southern high latitudes during the mid‐to‐late Holocene. The prominent features of the record serve as stratigraphic markers for hard‐to‐date Antarctic sedimentary records and a constraint on Holocene geomagnetic field behavior when incorporated into the next generation of geomagnetic field models.